THE EFFECT OF WOOD POWDER COMPOSITION AND PARTICLE SIZE ON THE ROUGHNESS OF CO₂ LASER BIOCOMPOSITES - Ahmad Saepuddin; Muhammad Khoirur Roziqin (Fakultas Teknik Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of pine wood powder composition and particle size on the surface roughness of biocomposites produced by CNC CO₂ laser cutting. The research method employed was an experimental design with variations in wood powder:PVA composition of 70:30, 60:40, and 50:50, and particle sizes of mesh 60, 140, and 200. The specimens were fabricated through manual mixing without the application of pressure during molding and were tested using a surface roughness tester with five measurement points for each variation. The data were analyzed using two-way ANOVA to determine the effects of each variable and their interaction. The results showed that both composition and particle size affected the surface roughness values. The best result was obtained for specimen B3 (60:40, mesh 200) with the lowest Ra value of 8.0566 µm, while the highest value was found in specimen C3 (50:50, mesh 200) at 16.780 µm. In addition, defects such as burning, void, and incomplete cut were identified and contributed to the overall surface quality. It can be concluded that the proper combination of material composition and particle size can improve the cutting quality of biocomposite materials.